Quality of life and symptom severity in premenstrual syndrome: a quasi-experimental study - Safaian, Zohre; Kohan, Mehri; Hoseinifard, Seyed Mehdi; Forouzi, Mansooreh Azizzadeh; Jahani, Yunes; Ahmadi, Atefeh (Online Brazilian Journal of Nursing, 2022)
Objective: The current study was conducted to investigate the effectiveness of group counseling on quality of life and symptom severity among university students with Premenstrual Syndrome. Method: After filling in PSST and participating in SCID-CV, 120 students answered the demographic and WHOQOL questionnaires. Using classified random sampling, they were divided into control and intervention groups. The Intervention Group participants attended six group counseling sessions. They post-tested at two moments (immediate post-test and after one month). Results: The results of the immediate post-test indicated improvements in overall quality and in some domains (p<0.005) in the Intervention Group, and the second post-test showed an improvement in two of the domains (p<0.005). One month later, some symptoms were clearly improved in the Intervention Group (p<0.005). Conclusion: Group counseling improved the students’ quality of life and severity of the Premenstrual Syndrome symptoms.